2011
DOI: 10.1364/josab.28.000450
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Optical precursors in the singular and weak dispersion limits”

Abstract: We point out inconsistencies in the recent paper by Oughstun et al. on Sommerfeld and Brillouin precursors [J. Opt. Soc. Am. B 27, 1664-1670(2010]. Their study is essentially numerical and, for the parameters used in their simulations, the difference between the two limits considered is not as clear-cut as they state. The steep rise of the Brillouin precursor obtained in the singular limit and analyzed as a distinguishing feature of this limit simply results from an unsuitable time scale. In fact, the rise of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…1∀ ω [16]. As in the study of the quasiresonant precursors [48], the equation giving the saddle points can then be reduced to a biquadratic form, and the saddle-point method is expected to provide simple solutions even when the Sommerfeld and Brillouin precursors partially overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1∀ ω [16]. As in the study of the quasiresonant precursors [48], the equation giving the saddle points can then be reduced to a biquadratic form, and the saddle-point method is expected to provide simple solutions even when the Sommerfeld and Brillouin precursors partially overlap.…”
Section: Discussionmentioning
confidence: 99%
“…An abundant bibliography can be found in the recent work by Oughstun [13]. Complementary studies on the effects of a finite turn-on time of the incident field on the precursors are reported in [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…(8) it is usually reduced with the help of the convolution theorem to (see, for example, Refs. [9][10][11])…”
Section: Light Beam In a Thick Resonant Mediummentioning
confidence: 99%
“…More than a century after their discovery, these transients, currently named Sommerfeld and Brillouin precursors, continue to raise considerable interest, due in particular to their sub-exponential attenuation with the propagation distance. An abundant bibliography on the subject is given in Ref [5] and more recent related studies are reported in Refs [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact the simultaneous observation of welldistinguishable Sommerfeld and Brillouin precursors, as considered by their discoverers, requires experimental conditions that seem unrealizable in optics [8]. A qualitative demonstration of separated Sommerfeld and Brillouin precursors has only been performed in microwaves by using guiding structures with dispersion characteristics similar to those of a Lorentz medium [11].…”
Section: Introductionmentioning
confidence: 99%